Multistate worklife expectancies - Nurminen, Markku; Nurminen, Tuula (Scandinavian Journal of Work, Environment & Health, 2005)
This communication reviews the demographic concept of worklife expectancy and draws the epidemiologists’ attention to its usefulness in occupational health research and pension policy making. The distinctions between different analytic approaches to the quantification of expected workforce status and mobility are pointed out. A recently developed multivariate large-sample regression method for the analysis of worklife tables is placed into the general context of life tables. Given aggregated data from multiple cross-sectional or longitudinal population surveys, a multistate regression model can be used to estimate consistently marginal probabilities that a person is in a given work–health state or transition probabilities between the states and, thereby, worklife expectancies. The methodology is illustrated through the application to data from Finnish population statistics on employment, disability, retirement, and mortality. The paper closes with a discussion of the methodological issues and empirical findings on pension policy in Finland.
Keywords: demography; disability; labor force activity; Markov model; multistate life table; regression methodology; retirement; review; statistics in society; unemployment; worklife expectancy